Effect of problem-based learning on Ugandan secondary school physics classroom practices: an observational study - Kanyesigye, Stella T.; Uwamahoro, Jean; Kemeza, Imelda (F1000Research, 2023)
Background: Regular class observations are common ways of monitoring what happens inside classrooms during the teaching and learning processes. From the start of 2020, the Ugandan Education System introduced a new curriculum focusing on active learning methods which foster learner-centered approaches, including Problem-Based Learning (PBL). However, this new curriculum is now only emphasized in the lower classes (grades eight and nine), and teachers of the upper classes are still at liberty to use methods of their choice. This study documented the effect of problem-based learning on Ugandan secondary school physics classroom practices using a Reformed Teaching Observation Protocol (RTOP). Methods: The study followed a quantitative approach with a quasi-experimental design employing cross-sectional survey techniques. The study was carried in 19 secondary schools, both government and private, in Mitooma District, southwestern Uganda. The participants were 419 13th-grade physics students of 2020/2021 school year together with 22 teachers. Professional training in implementing and assessing PBL lessons were offered to some teachers (experimental group), who were compared to those who did not receive the training (control group). The standard and validated international RTOP was used to observe 152 physics lessons. Microsoft Excel 2016 was used to compute descriptive analysis, while IBM SPSS 25 was used to compute inferential statistics. Results: The results indicated that teachers in the experimental group effectively taught their classes using PBL and learners were more active compared to the control group. Female teachers showed a statistically significant difference compared to their male teachers in reformed teaching of physics, while no significance was found between government and private schools. Conclusion: Giving teachers professional training is key to effective classroom practices. We recommend teachers to use PBL in teaching, policymakers train teachers on its implementations, and researchers investigate its effect on other subjects with RTOP or other standard observation protocols.
Keywords: Classroom observation; Physics class; Physics teacher; Problem-based learning; Uganda